PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENELITIAN DAN PENGEMBANGAN PROVINSI SULAWESI TENGGARA - Zulkifli Zulkifli (Mega Aktiva, 2018)
This study aims to determine the Effect of motivation on the performance of employees at the Badan Penelitian dan Pengembangan Provinsi Sulawesi Tenggara. The population in this study is all employees in the office Badan Penelitian dan Pengembangan Provinsi Sulawesi Tenggara as many as 53 people at the same times as respondents ( census method). Data collected by using Questionnaires. Data analysis using simple linear regression analysis. The study showed that the motivation significantly influence the performance of employees at the Badan Penelitian danPengembangan Provinsi Sulawesi Tenggara. The magnitude of the effect of work motivation on employee performance it can be seen from the coefficient of determination ( r2 ) = 0,885 at 88,50% which means that the performance of employees at the office Badan Penelitian dan Pengembangan Provinsi Sulawesi Tenggara 88,50% determined by motivation and the rest 11, 50 % determined by other variables or beyond the research model